Rule-based Dispute Settlement Mechanism for ASEAN Economic Community: Does ASEAN Have It? - Koesrianti, Koesrianti (Hasanuddin Law Review, 2016)
ASEAN Charter 2007 as ‘constitution’ of ASEAN aims to establish ASEAN Community (AC) in 2015 that ASEAN constitutes as a rule-based organization. ASEAN Community consists of three pillars, namely, ASEAN Political Security Community (APSC), ASEAN Economic Community (AEC), and ASEAN Socio Cultural Community (ASCC). AEC will posses as the lead for the Communities. The objective of AEC is to form a single market and production base with some priority sectors. Accordingly, many economic regional organizations provide Dispute Settlement Mechanism (DSM) to resolve disputes that may arise among the member countries. The dispute mechanism aims to provide predictability and security in international trade by providing strict time-frames, and was designed to be mutually agreed by the disputing members, flexible and binding. ASEAN trade DSM is designed as a legalistic mechanism. This paper examines DSM in ASEAN, especially economic disputes in the context of international trade law. In doing so, this paper analyzes DSM provided in the ASEAN Charter by comparing to DSM in the WTO context.